Advances in Retrieving Soil Moisture Content in the Yellow River Basin Using Remote Sensing Satellite Data - Zhang, Wenqing (International Journal of Natural Resources and Environmental Studies, 2025)
Yellow River Basin, which suffered from water shortage and drought disaster frequently, has a need to use soil moisture information precisely to assist the agriculture, drought monitoring, and climate research. The high resolution dataset is very useful for the resource management. Conventional ground based monitoring is difficult and limited on precision due to their spatial resolution and costs, but remote sensing is able to overcome due to its scalability; however due to the limitation of satellite dataset resolution, remote sensing plays a limited role in soil moisture observation. Here, we review the latest approaches in soil moisture retrieval with optical, microwave and GNSS-Reflectometry (GNSS-R) technologies and put particular emphasis on their applications in YRB. Optical approaches offer fine spatial resolution but cannot penetrate in clouds and canopy cover, while microwave and GNSS-R technologies can measure all weather with an effective depth up to 5 cm. The practicality of case studies are demonstrated in regional case studies (AVHRR-based deep-layer retrievals in 1982–1989 and multi-source data fusion in 2016–2018). In both cases, challenges are unresolved such as, insufficient resolution and/or inconsistent datasets. Further studies need to: 1) employ a region-specific model suitable for local hydrological characteristics, 2) enhance root-zone moisture estimation for near real time applications, and 3) provide a region-wide dataset based on multi-sources data fusion. Such breakthroughs are important in order to achieve increased farming resilience and sustainability in the basin.